UNDERSTANDING LEARNING STYLES: THEORIES, ANALYSIS, and EDUCATIONAL IMPACT - Davronova Marjona Sherzod qizi (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Individuals’ preferred methods of perceiving and processing information are indicated by their learning styles. Because they have a substantial impact on a person’s academic performance, engagement, and overall educational achievements, these individual preferences and dispositions are vital to the learning process. In educational psychology, the idea of learning styles has a lengthy and developing history.